Machine Learning Workout: with exercises and practicals in MATLAB - Ortega Martínez, Holger (2019)
In the crowded population of texts on Machine Learning, the present book is unique in the sense that it keeps the spirit of the books on basic subjects, like Calculus: its core is made up of many problems with answers, so that the reader can exercise and detect any misunderstanding on time. The book, then, es not for passive reading. It is meant for learning through exercising. Hard workout. Therefore, each chapter presents a set of exercises to be solved “by hand” (think of a desk check) and a strong set of programming tasks to be solved using MATLAB. Being intended for undergraduates, the book does not dive into deep mathematical waters. It is aimed instead to a deep comprehension of the concepts: the mechanics of the algorithms, the structure and geometric representation of the data, the precise evaluation of the results. All by doing it yourself, like in the good old days.